Determination of Standard Parameters of Acorn Squash Leaves - Oleh S. Shpychak (Journal of Global Pharma Technology, 2020)
One of the priority tasks of pharmacy is to find new sources of raw materials for the medicinal products. The purpose of this work is to determine a number of indicators of the quality of promising medicinal raw materials that are the leaves of acorn squash Cucurbita pepo (Cucurbitaceae) for the creation of regulatory and technical documentation. For our research one of the most competitive kind - "Ukrainian multi-plant" was chosen. This kind is not sensitive to climatic conditions (drought-resistant). It has been grown in many countries with moderate climate and the most parts of Ukraine (Polissya, forest-steppe, steppe) and other since 1950. In this way, for the first time, 7 series of acorn squash leaves of "Ukrainian multi-plant" were studied. The main diagnostic features of morphological structure, including morphometric indicators, the main diagnostic microscopic features of the powder of acorn squash leaves were determined. The work presents the limit values of the main figures of 7 series of raw materials: weight loss during drying (not more than 8.5 %), total ash content (not more than 3.7 %,), extractive substances content (not less than 20.0%), phenolic compounds content (not less than 2.0 %). According to the results obtained the regulatory and technical documentation “Methods of quality control of” Acorn squash leaves “has been developed. Keywords: Acorn squash, Leaf, Morphological structure, Microscopic diagnostic signs, Plant raw materials.